PERANCANGAN PERANGKAT LUNAK VISUALISASI ALGORITMA GREEDY - ANDY PAUL HARIANJA (JSIK (Jurnal Sistem Informasi Kaputama), 2019)
Visualization Software Design Greedy Algorithm is a depiction planning of software with engineering in making images, diagrams or animations to display an information in the form of a logical and systematic arrangement to solve a problem by finding the optimum solution. The goal is to create a visualization software design program that can optimize the preparation of goods in containers and their completion steps so as to facilitate problem solving, especially in real life. Greedy algorithm to solve the problem step by step or step by step, that every step will take the best option which can be obtained at the time ata get a solution quickly on the same day. The Greedy Algorithm will be used to find the optimum solution for the preparation of goods in containers that will get the most optimal results especially to reduce empty space. Goods are arranged according to height, width and length. Making visualizations developed using software is an effective way to help users to better understand and be able to learn independently.Keywords: design, visualization, algorithm, greedy